THE CLASH OF CIVILIZATION IS AN ENEMY DISCOURSE THAT LOOK FOR NEW ENEMIES - Memoona Kanval; Shabana Yasin; Dr. Kalsoom Hanif; Dr Raja Adnan Razzaq (International Journal of Contemporary Issues in Social Sciences, 2024)
In Huntington’s article the clash of civilization? which he refined and extended in 1996 a theory was presented which has many arguable points as he explored the role of culture in shaping conflict between civilizations and the role of the religion of Islam in the conflict. The argument contradicts his theory that the main reason for the conflict is not the clash of civilization but the clash of interests. According his theory Islam portrayed as the cause of tension between the west and Muslims countries but in reality religion has nothing to do with these conflicts. In modern world The theory of clash of civilization don’t apply it needs more clarification and more explanation. Qualitative research method has been employed in this article with the case study using secondary data sources. This research study has critically analyzed the events happened in 21st century on the basis of clash of civilizations. we cannot ignore the other factors in these 21st century events. Culture is not the prime source of conflict; depletion of resources, economy, military and geography are also very strong factors along with the culture which emerged after the cold war like War on Terror 2001 and Iraq war 2003 can be discussed as a case study to negate the idea of Huntington’s Clash of Civilization. It was actually an enemy discourse that is curious and searching new enemies for new world order.